Ingresos y gastos operativos y su incidencia en los resultados de la Empresa Formicimientos S.A. - Hidalgo Sánchez, Corina Lisbeth (2021)
The current research project focuses on operating income and expenses, as well as their impact on the results of the Guayaquil-based company Formicimientos S.A., which specializes in orthodontics. The goal is to examine the operating costs that influence a company's profitability. The following problem arises: The company Formicimientos S.A. does not have an accounting system and not having a reliable database for the tax return, this can cause problems with the control bodies. The company Formicimientos S.A……….